2015
DOI: 10.1038/srep18705
|View full text |Cite
|
Sign up to set email alerts
|

An integrated statistical model for enhanced murine cardiomyocyte differentiation via optimized engagement of 3D extracellular matrices

Abstract: The extracellular matrix (ECM) impacts stem cell differentiation, but identifying formulations supportive of differentiation is challenging in 3D models. Prior efforts involving combinatorial ECM arrays seemed intuitively advantageous. We propose an alternative that suggests reducing sample size and technological burden can be beneficial and accessible when coupled to design of experiments approaches. We predict optimized ECM formulations could augment differentiation of cardiomyocytes derived in vitro. We emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…In human tissue constructs, velocity of action potential propagation improved with increasing amounts of virtually pure CMs in the initial cell composition, whereas contractile force output was optimal for CM populations with purities of 60 to 80% (12). Overall, the presence of fibroblasts or other stromal cells in iPSC-derived cardiac tissues is found to be beneficial to CM maturation, via engagement of extracellular matrix proteins (13) and establishment of intercellular contacts, while excess of non-myocytes may compromise conduction and integration.…”
Section: Tackling Tissue-engineered Heart Repairmentioning
confidence: 99%
“…In human tissue constructs, velocity of action potential propagation improved with increasing amounts of virtually pure CMs in the initial cell composition, whereas contractile force output was optimal for CM populations with purities of 60 to 80% (12). Overall, the presence of fibroblasts or other stromal cells in iPSC-derived cardiac tissues is found to be beneficial to CM maturation, via engagement of extracellular matrix proteins (13) and establishment of intercellular contacts, while excess of non-myocytes may compromise conduction and integration.…”
Section: Tackling Tissue-engineered Heart Repairmentioning
confidence: 99%
“…Then by applying a “design of experiments” statistical approach to the platform, systematic optimization of the ECM ratios led to the identification of a formulation of cECM proteins optimized for cardiomyocyte differentiation. The theoretical formulation was confirmed experimentally via immunophenotyping and functional analyses [37]. Natural multicomponent ECMs derived from tissues have also been used in 3D to influence cell differentiation toward cardiomyocytes.…”
Section: In Vitro Control Systems To Evaluate Cell-cecm Interplay At mentioning
confidence: 97%
“…To further identify the optimal differentiation conditions for rESCs to cardiomyocytes, we first compared the effects of gelatin and laminin, which have been suggested to facilitate cardiomyocyte differentiation as supportive ECMs. 26,27 Most of the rEBs generated by the hanging droplet methodology ( Figure 2A) and cultured in gelatin coated dishes fail to attach ( Figure 2B). We found that laminin-induced rESC could induce the cardiomyocytes to beat on day 8 of differentiation, and the medium harbouring Laminin/differentiation-IMDM-FBS (DIF) produced 55.3% of beating rEBs derived from rESCs ( Figure 2E) Interestingly, rEBs cultured in laminin-coated dishes attached and proliferated well ( Figure 2B).…”
Section: Laminin Promoted Rebs Proliferation and Differentiationmentioning
confidence: 99%